The Factors Influencing Income Smoothing Action Of Pharmaceutical Companies Listed In IDX - Saifudin, Udin (Universitas Semarang, 2017)
This research aims at analyzing the factors influencing income smoothing action in those companies registered in IDX, particularly those running in pharmaceutical sector industry. The variables used in this research are share price, ownership structure, company size, profitability and leverage.This research uses quantitative approach with logistic regression analysis model. This research uses 2009-2013 period. The number of companies observed in this research is 9 companies.The results of this research show that the share price and profitability variables have no influence on income smoothing action, yet the ownership structure, company size, and leverage variables influence income smoothing action.